Cases in U.S. national security concepts and processes - Snow, Donald M. (Rowman & Littlefield, 2019)
"A series of brief case studies representing current and controversial policy problems facilitates deliberation and debate about competing policy ideas, and encourages undergraduate students to think critically about issues of national security. Cases include new strategies for containing the terrorist threat, the implications of President Trump's withdrawal from the Iran Nuclear Agreement, and the increasingly adversarial relations with Russia, focusing on Russian expansionism in its geographical domain and its interference in the 2016 American presidential election."--Provided by publisher